2008
DOI: 10.1016/j.ceca.2007.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes co-localize with ryanodine receptor subtype 3 to form a trigger zone for calcium signalling by NAADP in rat pulmonary arterial smooth muscle

Abstract: SummaryIn arterial myocytes the Ca 2+ mobilizing messenger NAADP evokes spatially restricted Ca 2+ bursts from a lysosome-related store that are subsequently amplified into global Ca 2+ waves by Ca 2+ -induced Ca 2+ -release from the sarcoplasmic reticulum (SR) via ryanodine receptors (RyRs). Lysosomes facilitate this process by forming clusters that co-localize with a subpopulation of RyRs on the SR. We determine here whether RyR subtypes 1, 2 or 3 selectively co-localize with lysosomal clusters in pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
109
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 21 publications
(34 reference statements)
13
109
0
Order By: Relevance
“…Previous work by our and other laboratories have identified all three RyR subtypes in PASMCs, with RyR2 being the most abundant subtype (23,39). RyR1 and RyR2 are associated mainly with SR in the subsarcolemmal region, whereas RyR3 is localized predominantly in the perinuclear SR (23,40 There is substantial evidence suggesting that Ang II enhances ROS production through activation of NOX, contributing to Ca 21 response in VSMCs (17). Several studies have shown that CD38 activity is regulated by redox state and oxidative stress (19,20,22,27,43).…”
Section: Discussionmentioning
confidence: 66%
“…Previous work by our and other laboratories have identified all three RyR subtypes in PASMCs, with RyR2 being the most abundant subtype (23,39). RyR1 and RyR2 are associated mainly with SR in the subsarcolemmal region, whereas RyR3 is localized predominantly in the perinuclear SR (23,40 There is substantial evidence suggesting that Ang II enhances ROS production through activation of NOX, contributing to Ca 21 response in VSMCs (17). Several studies have shown that CD38 activity is regulated by redox state and oxidative stress (19,20,22,27,43).…”
Section: Discussionmentioning
confidence: 66%
“…7; supplementary material Movie 1), allowing lysosomes selectively to accumulate Ca 2+ released from the ER. The reciprocal relationship is also important because in many cells NAADP-evoked Ca 2+ release from lysosomes triggers Ca 2+ release from the ER by Ca 2+ -induced Ca 2+ release via Ins(1,4,5)P 3 R (Calcraft et al, 2009) or RyR (Brailoiu et al, 2010;Cancela et al, 1999;Kinnear et al, 2008;Lee et al, 1997). Lysosome-ER junctions are reminiscent of those between mitochondria and ER (Fig.…”
Section: + Signallingmentioning
confidence: 99%
“…8). Ca 2+ release via TPC2 can trigger Ca 2+ release via RyR or Ins(1,4,5)P 3 R in the ER (Brailoiu et al, 2010;Calcraft et al, 2009;Kinnear et al, 2008), and Ca 2+ release via Ins(1,4,5)P 3 R is selectively accumulated by lysosomes. The latter may regulate the behaviour of lysosomes by increasing lysosomal pH; by priming TPC2, which appears to be stimulated by luminal Ca 2+ (Pitt et al, 2010), to respond to NAADP; and it may regulate endolysosomal trafficking (Luzio et al, 2010).…”
Section: + Signallingmentioning
confidence: 99%
“…These findings have led to the 'NAADP trigger hypothesis', whereby Ca 2+ released by the action of NAADP can recruit IP 3 R and RyR-mediated signalling pathways via CICR (Churchill and Galione 2001). Differences in the extent of ER store involvement in different cell types is likely to be a consequence of different patterns of localisation of the stores and receptors, with recruitment occurring when NAADP-mediated Ca 2+ release occurs in close proximity to ER channels (Kinnear et al, 2004, Kinnear et al, 2008, Morgan et al, 2011 (Morgan et al, 2013). This effect may be dependent on local microdomains of high [Ca 2+ ]i at junctions between the ER and acidic organelles.…”
Section: Acidic Endolysosomal Ca 2+ Stores and Naadpmentioning
confidence: 99%